ANALISIS KELEMBABAN DAN SEBUM KULIT PADA PENDERITA DERMATITIS SEBOROIK - Indriani, Andi Ratu Panca; Sitti Musafirah (Bahasa Indonesia, 2024)
ABSTRACT Background: Skin hydration and sebum are crucial for maintaining the integrity of the stratum corneum. Abnormalities in the stratum corneum lead to skin inflammation such as seborrheic dermatitis, characterized by symptoms like dandruff, oily yellow scales, erythroderma, affecting individuals across various age groups. Purpose: To analyze skin moisture and sebum in patients with Seborrheic Dermatitis. Method: This research employs an observational analytical approach using a case-control design. The total sample size comprises 87 individuals, including 37 patients with seborrheic dermatitis from the Skin Health, Gender, and Cosmetic Health Center in Makassar city, and 50 healthy controls. Results: The correlation between skin moisture levels and seborrheic dermatitis is significant (p-Value 0.000). The majority of patients exhibit dry skin (64.9%), whereas none of the controls experience the same. A small proportion of patients have normal skin (8.1%), in contrast to the controls (100%). Patients with slightly moist skin (27%) are absent among the controls. Similarly, the correlation between sebum levels and seborrheic dermatitis is significant (p-Value 0.000). The majority of patients exhibit excessive sebum (91.9%), unlike the controls. Few patients have normal sebum levels (8.1%), contrasting with the controls (100%). Conclusion: In patients with seborrheic dermatitis, the majority present with dry skin moisture (≤29%) compared to healthy individuals with normal moisture levels (30-60%), and oily sebum levels (≥34%) compared to healthy individuals with normal sebum levels (16-33%). There is a significant relationship between skin moisture and sebum levels and the occurrence of seborrheic dermatitis (p-Value 0.000). Keywords: skin moisture, skin sebum, seborrheic dermatitis